ZVS Full Bridge Series Resonant Boost Converter with Series-Connected Transformer - Mohamed Salem; Awang Jusoh; N.Rumzi N. Idris; Tole Sutikno; Iftikhar Abid (Institute of Advanced Engineering and Science, 2017)
This paper presents a study on a new full bridge series resonant converter (SRC) with wide zero voltage switching (ZVS) range, and higher output voltage. The high frequency transformer is connected in series with the LC series resonant tank. The tank inductance is therefore increased; all switches having the ability to turn on at ZVS, with lower switching frequency than the LC tank resonant frequency. Moreover, the step-up high frequency (HF) transformer design steps are introduced in order to increase the output voltage to overcome the gain limitation of the conventional SRC. Compared to the conventional SRC, the proposed converter has higher energy conversion, able to increase the ZVS range by 36%, and provide much higher output power. Finally, the a laboratory prototypes of the both converters with the same resonant tank parameters and input voltage are examined based on 1 and 2.2 kW power respectively, for veryfing the reliability of the performance and the operation principles of both converters.